Epidemiology of Hepatitis B and C Infection in Msallata city in reference to Age Groups and Genders (Al-Qalaa Journal, 2024)
The most important of viral hepatitis are ‎hepatitis C, D, and E viruses. ‎ The aims of the research, to understand number of infected cases with both hepatitis B and/or C viruses and non-‎infected in ‎terms of genders.‎ also, detected more age infected people groups, and the ‎hepatitis B or C virus infected for ‎both genders. ‎Materials and methods, the tests were carried out using ELISA technique.Results, the higher number of infected cases was males with 2.8 % from 392 samples of males. The higher number of cases was infected with B virus. Whereas, males infected more ‎than females with 63.6% of total number of cases infected by hepatitis B virus. Also, the ‎higher number of cases was infected with hepatitis C virus. Whereas, males infected more than females ‎with 85.7% of total number of cases infected by hepatitis C virus. The age groups of the samples observed the higher age group infected with hepatitis B ‎virus which was 35-45 years, which was 7 infected cases of total 14 cases infected, exactly 50% of ‎infected cases.‎‎